Traduire les albums pour enfants d’Hervé Tullet en polonais - Kochanowska, Anna (Studia Romanica Posnaniensia, 2021)
This paper concentrates on the translation of the text-image interaction in postmodern and multimodalpic turebooks for children, as illustrated by the Polish translations of Hervé Tullet’s picturebooks. The sophisticated and artistic vision of this author-illustrator raises questions about methods and criteria to be adopted by anyone who wishes to translate the delicate balance between what is told by the verbal and pictured by the visual. In particular, as the present analysis reveals, the translator’s interventions in the original text-image interaction cannot be regarded as intersemiotic translation, but as undesired explicitation limiting the creative actions of the active child-reader.